Creativity and Psychopathology: Sex Matters. Issue 2 (2nd April 2016) - Martín-Brufau, Ramón; Corbalán, Javier
Abstract : The association between creativity and psychopathology has, for decades, been a focus of heated debate fuelled by contradictory findings. Nevertheless, the findings suggest complex associations between creativity and psychopathology. Other studies have investigated the association between creativity and sex, with inconsistent results. The aim of this study was to investigate the influence of sex on the association between creativity and psychopathology. In total, 106 participants (37 men and 69 women) were administered the Symptom Check List (SCL90-R) and the CREA test of creativity. There were no significant associations in the total sample between the variable creativity and the psychopathology scales. Strikingly, when the sample was divided by gender, a moderate-to-high significant positive association between creativity and psychopathology was found among men. Previously, the associations between creativity and gender and between creativity and psychopathology were studied in relative isolation from each other, rather than together as the main focus of research. Our results suggest that the complex associations between psychopathology and creativity differ between men and women.